THE DETERMINATION OF LC50 OF DIAZINON AND IT'S SUB-LETTAL EFFECT ON HAEMATOLOGICAL INDICES OF BELUGA (HUSO HUSO) - M. Shamlofar; A. kamali; M. Piri; F. Yaghmaei; N. Makhdomi (Iranian Fisheries Research Organization, 2007)
The acute toxicity and effects of diazinon on some hematological indices of Beluga (Huso huso) juveniles weighting 4.3±0.12 grams was assessed following the O.E.C.D. direction in a static temperature in the range 20.27±2.05oCT.he 96h LC50 value of diazinon for beluga juveniles was 5.821. Also, the maximum allowable concentration of diazinon in natural waters for beluga was determined to be 0.5821 mg.l-1. Based on the toxicity table of insecticides, diazinon was listed as toxic for beluga .The clinical symptoms that were observed in this study consisted of lordosis and neural paralytic syndrome in fish exposed to the pesticide. Some abnormal reactions such as losing the balance when swimming and swimming in a half circle; expressive pigmentation mainly on the dorsal part were seen in the juveniles. Examination of hematological indices was performed on control and experimental specimens of beluga weighting 16.08 grams on average that were treated with 96h exposure to diazinon in a concentration lower than LC50 96h. The experimental group of beluga showed significantly lower value (P<0.05) of ,erythrocyte (RBC) and leukocyte count, hemoglobin content (Hb), and haematocrite (PCV), MCV, MCH and relative lymphocyte and eosinophil counts compared to the control group .In comparison, the relative heterophil count in the juveniles of the experimental group was significantly higher than the control group. By observing a decrease in the amount of leukocyte profile specially lymphocytes which are important in non-specific immunity of the fish, it can be said that diazinon may cause a decrease in the non-specific immunity of beluga.